2021
DOI: 10.1051/e3sconf/202124803039
|View full text |Cite
|
Sign up to set email alerts
|

Research status and prospect of waste steel fiber reinforced concrete

Abstract: Scrap steel fiber concrete (SFRC) is a new kind of concrete material, which uses the scrap steel fiber from the scrap tire as the reinforced fiber of FRP bar fiber reinforced concrete, replacing or partially replacing the traditional steel fiber and synthetic fiber. This paper summarizes the research status of waste steel fiber at home and abroad, including the mechanical properties of compressive and tensile resistance, the mixing amount and use requirements of waste steel fiber, and finally the development p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Their experimental results showed that while industrial recycled steel fibers had a minimal impact on compressive strength, they significantly influenced flexural strength. Compared to conventional concrete, recycled steel fiber concrete exhibited a gradual decline in bending toughness along the load-deflection curve, with a secondary peak emerging [15].…”
Section: Introductionmentioning
confidence: 93%
“…Their experimental results showed that while industrial recycled steel fibers had a minimal impact on compressive strength, they significantly influenced flexural strength. Compared to conventional concrete, recycled steel fiber concrete exhibited a gradual decline in bending toughness along the load-deflection curve, with a secondary peak emerging [15].…”
Section: Introductionmentioning
confidence: 93%
“…Material recovery, which uses secondary materials from ELTs in construction, automotive, and civil engineering applications, was used to treat around 2 million tons (61.75 percent of total ELTs handled). Apart from this, in 2009, China’s tire production by rubber consumption accounted for around 70% of the country’s total rubber resource consumption, resulting in 233 million waste tires weighing approximately 8.6 million tons, equivalent to approximately 3 million tons of rubber resources [ 7 ]. According to Pilakoutas et al [ 8 ], over a billion discarded tires are produced worldwide.…”
Section: Introductionmentioning
confidence: 99%